Antineoplastic activity of novel thiazole derivatives - Finiuk, N.S.; Hreniuh, V.P.; Ostapiuk, Yu.V.; Matiychuk, V.S.; Frolov, D.A.; Obushak, M.D.; Stoika, R.S.; Babsky, A.M. (Вiopolymers and Cell, 2017)
The development of novel efficient substances for anticancer chemotherapy is an important problem of medicinal chemistry. Aim. To evaluate the level of cytotoxic action of novel thiazole derivatives towards tumor cell lines of different origin. Methods. Four N acylated 2-amino-5-benzyl-1,3-thiazoles (5a–d) were synthesized by reaction of 2-amino-5-R-benzyl-1,3-thiazoles with acid chlorides in the presence of triethylamine in the dioxane medium. Anticancer screening of the synthesized thiazoles was performed by the MTT assay. Results. Thiazole derivatives were shown to exert antineoplastic activity towards different types of tumor cells. The anti-glioma and anti-melanoma selectivity of these derivatives action was demonstrated. The compound 5a was found to be the most toxic for human glioblastoma U251 cells and human melanoma WM793 cells. At the same time, the created compounds possessed low toxicity towards pseudo-normal cells. Conclusion. The novel thiazole derivative 5a was the most toxic against human glioblastoma and melanoma cells.